Observe Gamma-Rays and Neutrinos Associated with Ultra-High Energy Cosmic Rays - Qinyuan Zhang; Xishui Tian; Zhuo Li (Universe, 2022)
IceCube measures a diffuse neutrino flux comparable to the Waxman-Bahcall bound, which suggests the possibility that the ultra-high energy cosmic rays (UHECRs) have a common origin with diffuse high energy neutrinos. We propose high energy gamma-ray and/or neutrino observations toward the arrival directions of UHECRs to search for the sources and test this possibility. We calculate the detection probability of gamma-ray/neutrino sources, and find that the average probability per UHECR of >10 EeV is ∼10% if the sensitivity of the gamma-ray or neutrino telescope is ∼10<semantics>−12</semantics> erg cm<semantics>−2</semantics> s<semantics>−1</semantics> and the source number density is ∼10<semantics>−5</semantics> Mpc<semantics>−3</semantics>. Future gamma-ray and neutrino observations toward UHECRs, e.g., by LHAASO-WCDA, CTA, IceCube/Gen2, are encouraged to constrain the density of UHECR sources or even identify the sources of UHECRs.